A Linguistic Issue In By NafīS AL-Dīn Abū L-Faraj Ibn Al-Kaṯār (Thirteenth Century). (2nd September 2020) - Ali, Watad
Abstract: The treatise by Nafīs al-Dīn Abū l-Faraj Ibn al-Kaṯār, also known as Shams al-Ḥukamā, active circa the end of the thirteenth century CE, is written in Middle Arabic in the Arabic script. Verses of the Torah and quotes from Samaritan religious poems are written in Samaritan Hebrew letters. The treatise is extant in a number of Samaritan manuscripts kept in various libraries in Israel and abroad. While the title of this work is, its contents encompass numerous topics in a variety of fields: linguistics, exegesis, religious law and more. Among the linguistic issues it addresses, for example are topics in phonology, morphology, syntax and semantics. The present article discusses two interrelated linguistic issues in phonology and morphology, the first dealing with the conjugation of irregular verbs: the phonological discussion focuses on the concept of ' iwaḍ (compensation) and in morphology we discuss I/y verbs and, by the way, also I/n verbs. In addition, I examine this work's affinities with the grammatical theories expounded by the Samaritan grammarian Ibn Mārūṭ and the rabbinic grammarian Yehuda Ḥayyūj.